The Effect of Organizational Culture on Employee Performance through Work Motivation and Job Satisfaction - Saji Saputra; Yayan Hadiyat; Herdiyana (Asosiasi Ahli Administrasi Indonesia, 2026)
Employee performance plays an important role in determining organizational success. However, several performance indicators in the Risk Management Division of PT CJ Feed Indonesia have not reached expected targets, indicating potential issues related to organizational culture, work motivation, and job satisfaction. This study aims to examine the effect of organizational culture on employee performance through work motivation and job satisfaction as intervening variables. The research applied a descriptive quantitative approach using a survey method. The population consisted of 102 staff-level employees in the Risk Management Division of PT CJ Feed Indonesia across all sites, and all members of the population were used as respondents through a saturated sampling technique. Data were collected using questionnaires and analyzed using Structural Equation Modeling with Partial Least Square. The results show that organizational culture has a significant effect on work motivation and job satisfaction. Work motivation has a positive and significant effect on employee performance, whereas job satisfaction does not significantly influence employee performance. Furthermore, work motivation mediates the relationship between organizational culture and employee performance, while job satisfaction does not play a mediating role. These findings indicate that strengthening organizational culture supported by improving work motivation is more effective in enhancing employee performance. The study provides managerial implications for organizations to focus on internalizing cultural values and strengthening motivational factors to achieve better performance outcomes.